2017
DOI: 10.1002/14651858.cd011674.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Back Schools for chronic non-specific low back pain

Abstract: Due to the low- to very low-quality of the evidence for all treatment comparisons, outcomes, and follow-up periods investigated, it is uncertain if Back School is effective for chronic low back pain. Although the quality of the evidence was mostly very low, the results showed no difference or a trivial effect in favour of Back School. There are myriad potential variants on the Back School approach regarding the employment of different exercises and educational methods. While current evidence does not warrant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 54 publications
0
39
0
3
Order By: Relevance
“…Back schools use varying exercises and educational methods. There is very low-quality evidence that back school is more effective than no treatment (mean difference (MD) − 6.10, 95% confidence interval (CI) − 10.18 to − 2.01) in acute low back pain [ 21 ].…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Back schools use varying exercises and educational methods. There is very low-quality evidence that back school is more effective than no treatment (mean difference (MD) − 6.10, 95% confidence interval (CI) − 10.18 to − 2.01) in acute low back pain [ 21 ].…”
Section: Preventionmentioning
confidence: 99%
“…A recent Cochrane systematic review of RCTs evaluating the effectiveness of back schools was undertaken [ 21 ]. Low-quality evidence showed back schools to be no better than exercise in the intermediate-term (mean difference or MD − 4.46; 95% CI − 19.44 to 10.52), as well as at long-term follow-up (MD 4.58; 95% CI − 0.20 to 9.36) [ 21 ]. It remains unclear whether or not back schools are effective for chronic low back pain.…”
Section: Back Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many variations have evolved. A recent Cochrane review [151] reported generally very low quality of evidence for back schools, and found, at best, a trivial effect in the treatment of chronic LBP.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Since this review, there have been additional systematic reviews that have assessed some form of patient education. [28][29][30][31][32][33][34][35][36][37][38][39][40] However, most of these reviews have investigated more intensive formats of education or skills training programmes (eg, multisession and multicomponent education programmes or self-management interventions), 28 30 32-37 or a specific delivery method of education (eg, verbal and communicative education strategies) 29 38 rather than the provision of education materials. Similarly, some reviews only focused on a specific education topic such as neurophysiological pain education.…”
mentioning
confidence: 99%